To Leverage the Innovation Capability by Co-creation of Human-Machine - Jiaona Xiang, Zongqiang Ren, Shuxian Chen (Forest Chemicals Review, 2021)
Although a societal consensus has been reached about the partnership between human beings and smart machines, limited research has been carried out to consider advances in its combination pattern, function mechanism, and developing creativity. Based on occurred disruptive changes form theory to practice, a new paradigm of co-creation by synergistic human-machine is proposed, which refers to that interaction of human-machine learning in a holistic system increase complementarity of abilities and integration of wisdom to realize an augmented synergy made up of hybrid intelligences. This augmented intelligence can effectively account for shifts in business logic and the productive solutions to the multiple complex problems during smart manufacturing. It has been discovered that the positive consequences of synergistic human-machine co-creation include not only sustainable labor patterns, but the ability to overcome multiple complexities and steadily increase business value. All this is further elaborated in the Baizhentang Foods case. This paper discusses the main prospects of the theoretical developments presented here for future research on organizational behavior and a synergistic human-machine structure.